The Impact of Plastic Nanoparticles on Human Health and the Environment: Risks, Challenges, and Proposed Solutions - karim, Shimaa Abdullah (American Journal of Biodiversity, 2025)
Use of plastic has become an indispensable element in the routine life of the general public. The improper disposal of plastic products has become a significant environmental, health, and public management concern. The maritime sector generates around 6.4 million tons of marine waste annually worldwide. The disposal of plastic waste or small polymer particles into aquatic environs is not permitted. The decomposition process of polymeric waste, especially the plastic waste, results in the formation of plastic nanomaterials. After transformation, plastic matter transforms into two different segmentations directly: micro-size and nano-scale plastic. The approach of the use of bioplastics is considered as a general measure to counteract the issue of accumulation of toxic plastic waste. The nanoparticles transferred to the aquatic surroundings transcend through the thermal, optical, and biodegradation. The nanoparticles primarily react at the end of the life cycle of polymers. During the transformation stage of the polymers depiction procedure, the plastic material is exposed to thermal instability. The usage of assorted agglomerations of additives during the production of plastics reduces degradations caused by light, hotness and the bio-decomposability of the plastic material. This results in leaching out of the plastic particles at the final stages of decomposition. This mechanism of action of nanoplastic material generation operates in a direction similar to that of mechanical ablation. However, the mechanism of unnatural degradation of plastic in the ambient surrounding is a relatively slow process of particle fragmentation and agglomeration, which finally generates polymeric nanoparticles.